2022
DOI: 10.1155/2022/3855582
|View full text |Cite
|
Sign up to set email alerts
|

Functional Properties of Donor (Al) and Acceptor (Cu) Codoped High Dielectric Constant ZnO Nanoparticles

Abstract: In this work, we have synthesized donor-acceptor (Al-Cu) codoped ZnO nanoparticles with a doping concentration of 0%, 0.25%, 0.5%, and 0.75% by coprecipitation method. The synthesized samples were then annealed at 350°C and 600°C. All the samples showed wurtzite structure of ZnO with no secondary phase. The increase in doping concentration led to deterioration of crystalline quality, while improved crystallinity was observed at higher annealing temperature. The morphological study of these samples showed good … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Studies have shown that co-doping ZnO nanoparticles with Mn & Co [ 62 ], Fe & Co [ 63 ], and Ni & Co [ 64 ] exhibit better antimicrobial, photocatalytic, and ferromagnetic properties compared to pure and mono-doped ZnO NPs. Co-doping with Ni & Cu [ 65 ], Y & Cu [ 66 ], and Al & Cu [ 67 ] show higher dielectric constant, ferromagnetism, and better optical properties suitable for optoelectronic device development. On the other hand, co-doping ZnO nanoparticles with Al & Ag [ 68 ], Ni & Ag [ 69 ], and Y & Ag [ 69 ] have been observed to have better electrical, optical, and photocatalytic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that co-doping ZnO nanoparticles with Mn & Co [ 62 ], Fe & Co [ 63 ], and Ni & Co [ 64 ] exhibit better antimicrobial, photocatalytic, and ferromagnetic properties compared to pure and mono-doped ZnO NPs. Co-doping with Ni & Cu [ 65 ], Y & Cu [ 66 ], and Al & Cu [ 67 ] show higher dielectric constant, ferromagnetism, and better optical properties suitable for optoelectronic device development. On the other hand, co-doping ZnO nanoparticles with Al & Ag [ 68 ], Ni & Ag [ 69 ], and Y & Ag [ 69 ] have been observed to have better electrical, optical, and photocatalytic properties.…”
Section: Introductionmentioning
confidence: 99%